2020
DOI: 10.4414/smw.2020.20378
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of clinical manifestations and treatment strategies for invasive beta-haemolytic streptococcal infections in a Swiss tertiary hospital

Abstract: AIMS OF THE STUDY Invasive streptococcal infections affect more than half a million patients worldwide every year and have a high lethality. Little is known about the epidemiology and microbiological characteristics of streptococcal infections in Switzerland. This case series study aims to describe the demographics, known risk factors for streptococcal skin and soft tissue infections, clinical presentations, treatment and outcomes of patients admitted to the University Hospital Zurich between 2000 and 2014 wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
1
Order By: Relevance
“…invasive infections (Laupland et al 2019;Martín Guerra et al 2019;Neff et al 2020;Zhu et al 2021). Contrary to our findings, other studies showed a much lower percentage of contamination with bacilli, micrococci, and streptococci on the surfaces of stethoscopes.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…invasive infections (Laupland et al 2019;Martín Guerra et al 2019;Neff et al 2020;Zhu et al 2021). Contrary to our findings, other studies showed a much lower percentage of contamination with bacilli, micrococci, and streptococci on the surfaces of stethoscopes.…”
Section: Discussioncontrasting
confidence: 99%
“…For most people, these bacteria are not etiologic agents of infections. However, for children, immunosuppressed patients, or patients undergoing invasive medical procedures during hospitalization, micrococci, and streptococci can cause severe invasive infections ( Laupland et al 2019 ; Martín Guerra et al 2019 ; Neff et al 2020 ; Zhu et al 2021 ). Contrary to our findings, other studies showed a much lower percentage of contamination with bacilli, micrococci, and streptococci on the surfaces of stethoscopes.…”
Section: Discussionmentioning
confidence: 99%
“…Necrotizing fasciitis (NF) caused by the human pathogen Group A Streptococcus (GAS, aka Streptococcus pyogenes ) remains a devastating disease, associated with high morbidity and mortality despite the use of effective antibiotics and surgery [1]. Bacteria employ several strategies to escape killing, including antibiotic resistance development, intracellular localization and biofilm formation, the last two protecting them from antibiotic exposure and the immune system [2].…”
Section: Introductionmentioning
confidence: 99%